لمحات عن خصائص التصوف ومراجعه المعتبرة في بلدان الملايو: A Glimpse on the Characteristics of Sufism and Its Major References in the Malay World - al-Akiti, Muhammad Ayman; Abdul Halim, Zainul Abidin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Sufism (taṣawwuf) is one of three major discussions of Sunni scholars in the Malay world. These scholars have given an impressive focus to the discussion of Sufism which is a complement to the discussion of ‘aqidah and fiqh. As a result, they succeeded in generating new ideas in Sufism and contributing to the intellectual development of this discipline. This paper discusses the principle of Sufism by Malay Sunni Sufi scholars who follow the methodology of Imam al-Ghazālī and al-Shaykh al-Akbar Ibn ʻArabī al-Ḥātimī. The focus of discussion will be on how the Malay scholars understand the objective methodology of Sufism by al-Ghazālī and Ibn ʻArabī and how they make these objectives realized through the establishment of Sufism syllabus for the Malay community. It categorizes the Sufis into three levels where each of these levels has a text of study corresponding to it. This study also explains that the study of Sufism is based on the category of knowledge level and the level of students. This is as explained by the two figures. Thus, the study concludes that the contribution of Malay scholars has merged the concept of the level of knowledge and its students based on the thought of Imam al-Ghazālī with the concept of categorization of knowledge and its students by Imam Ibn ʻArabī al-Ḥātimī. At the same time, this study proves taṣawwuf kashfī that comes with the spread of Islam to the Malay world is never lost, but it continues to grow, and studied until now.